2022
DOI: 10.30574/gscbps.2022.19.3.0232
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative phytochemical screening and in vitro thrombolytic activity of Capparis decidua Edgew. Fruit

Abstract: Abnormal thrombosis plays an important role in development of ischemic heart disease and stroke. Synthetic thrombolytic agents are effective but possess some adverse effects. Therefore, the need for development of comparatively safer anti-thrombotic drugs from natural resources such as plants arises. Capparis decidua Edgew. (Family – Capparaceae) is a densely branched, xerophytic shrub and grows abundantly in arid and semiarid regions. Its fruits are major ingredient of the popular ‘Panchkuta’ vegetable of Raj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, significant in vitro clot lysis activity of 39.70±0.99 and 32.39±2.10% were shown by methanolic extract of two plants that are consumed in diet, viz., leaves of Chenopodium album and fruits of Capparis decidua, respectively 3,22 . In these studies, it was evident that the addition of water to the clot did not cause clot disintegration which was also observed in the present study with negligible clot lysis shown by distilled water (4.05%).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, significant in vitro clot lysis activity of 39.70±0.99 and 32.39±2.10% were shown by methanolic extract of two plants that are consumed in diet, viz., leaves of Chenopodium album and fruits of Capparis decidua, respectively 3,22 . In these studies, it was evident that the addition of water to the clot did not cause clot disintegration which was also observed in the present study with negligible clot lysis shown by distilled water (4.05%).…”
Section: Discussionmentioning
confidence: 99%